Watching TV and Food Intake: The Role of Content - Chapman, Colin D.; Nilsson, Victor C.; Thune, Hanna Å.; Cedernaes, Jonathan; Le Grevès, Madeleine; Hogenkamp, Pleunie S.; Benedict, Christian; Schiöth, Helgi B. (PloS one, 2014)
Obesity is a serious and growing health concern worldwide. Watching television (TV) represents a condition during which many habitually eat, irrespective of hunger level. However, as of yet, little is known about how the content of television programs being watched differentially impacts concurrent eating behavior. In this study, eighteen normal-weight female students participated in three counter-balanced experimental conditions, including a 'Boring' TV condition (art lecture), an 'Engaging' TV condition (Swedish TV comedy series), and a no TV control condition during which participants read (a text on insects living in Sweden). Throughout each condition participants had access to both high-calorie (M&Ms) and low-calorie (grapes) snacks. We found that, relative to the Engaging TV condition, Boring TV encouraged excessive eating (+52% g, P = 0.009). Additionally, the Engaging TV condition actually resulted in significantly less concurrent intake relative to the control 'Text' condition (-35% g, P = 0.05). This intake was driven almost entirely by the healthy snack, grapes; however, this interaction did not reach significance (P = 0.07). Finally, there was a significant correlation between how bored participants were across all conditions, and their concurrent food intake (beta = 0.317, P = 0.02). Intake as measured by kcals was similarly patterned but did not reach significance. These results suggest that, for women, different TV programs elicit different levels of concurrent food intake, and that the degree to which a program is engaging (or alternately, boring) is related to that intake. Additionally, they suggest that emotional content (e.g. boring vs. engaging) may be more associated than modality (e.g. TV vs. text) with concurrent intake.